Children’s birth weight and their current body mass index in relation to early childhood caries - Mohd Shukri, Nor Azwani; Lokman, Nazalikha; Mustafa, Norashikin; Rusali, Roszanadia; Harun, Nor Asilah (Ectodermal Dysplasia Group-Turkey, 2020)
Early childhood caries (ECC) is considered the most common chronic disease in childhood globally. Earlier reports have associated ECC with weights at birth and during early childhood, but these have never been assessed in our local populations. Thus, the aim of this study was to find the associations between birth weight and current body mass index (BMI) and the occurrence of ECC among young children in Kuantan, Pahang. A total of 200 children aged from two to five years were recruited for this research. Visual examination for caries detection was conducted to determine the present of caries. The information on demographic data such as age, parental education levels, socioeconomic status, and anthropometry data such as birth weight, current height and weight of the participants were obtained from the parents through a self-administered questionnaire. The findings indicate that ECC was prevalent among 83% of the study participants. In addition, the children who were diagnosed with ECC had significantly (p=0.008) lower mean BMI (16.0 ± 12.0 kg/m²) compared to caries free children (18.7 ± 9.3 kg/m²). There is no association between ECC and birth weight but children with ECC were significantly more likely to be underweight compared to caries free children.